Legal capacity of nonprofit organizations - Кацюба, К. В. (Theory and practice of jurisprudence, 2016)
Problem setting. The relevance of the chosen theme is the advisability of fixing the limits of enterpreneur actions which is carried out by non-profit organizations. Recent research and publications analysis. This article analyzes recent researches of the legal status of non- profit organizations in the works of V. Borisova, I. Kucherenko, I. Spasibo-Fateeva, I. Zhyhalkina, V. Poddubny, V. Cochin and etc., which underlines the importance of scientific research. Paper objective. The article aims was to identify contradictions in the current legislation of Ukraine and how to overcome them. Paper main body. The legislation of Ukraine, the Civil Code of Ukraine and a number of special normative acts governing the activities of non-profit organizations, grants the right them to engage in business activities. In modern terms, this fact is important, as it provides the ability to create resources to implement the main statutory activities of non-profit organizations for more intensive and fruitful implementation of its statutory objectives. The question is to determine the limits of necessary and legitimate participation of non-profit organizations in the business. The legislation proposed in this paper is to provide a means of influencing non- profit organizations in case of abuse of the right to do business. Conclusions of the research. It is necessary for our legislation to make amendments and to set out the limits of power of non- profit organizations. Also, it is necessary to define the form of entrepreneurship. Business activities of business companies, non profit or created with their participation may be made only for profit and not be associated with non- profit organization authorized activity. Creation of business associations seems necessary not only in terms of exclusion existing contradictions in the civil legal regulation of non- profit organizations, but also in terms of the effectiveness of ongoing business activities. Business organizations may have a larger legal capacity and is not limited in the types of business activities.